2020
DOI: 10.1371/journal.pone.0235129
|View full text |Cite|
|
Sign up to set email alerts
|

Ecological responses to blue water MPAs

Abstract: Marine protected areas (MPAs) can contribute to protecting biodiversity and managing ocean activities, including fishing. There is, however, limited evidence of ecological responses to blue water MPAs. We conducted the first comprehensive evaluation of impacts on fisheries production and ecological responses to pelagic MPAs of the Pacific Remote Islands Marine National Monument. A Bayesian time series-based counterfactual modelling approach using fishery-dependent data was used to compare the temporal response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 118 publications
(171 reference statements)
1
19
0
Order By: Relevance
“…However, given the historical differences in catch rates, species composition and spatial overlap between the LBF and DWF, future assessments of the PNMS may benefit, alongside other methods of census, from dedicated research fishing trips by the LBF in areas of the PNMS where fishing effort was once concentrated. Alternatively, a counterfactual approach could be used to assess the responses of various species to the PNMS by predicting what the LBF's catch would have been, had the designation of the sanctuary and the re-location of the DFZ not eliminated its fishing grounds (Gilman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the historical differences in catch rates, species composition and spatial overlap between the LBF and DWF, future assessments of the PNMS may benefit, alongside other methods of census, from dedicated research fishing trips by the LBF in areas of the PNMS where fishing effort was once concentrated. Alternatively, a counterfactual approach could be used to assess the responses of various species to the PNMS by predicting what the LBF's catch would have been, had the designation of the sanctuary and the re-location of the DFZ not eliminated its fishing grounds (Gilman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The local abundance of prey resources may have increased within the MPAs as a result of the cessation of fishing mortality, while at a "control" penguin colony with no MPA there may have been increased fishing mortality due to displaced fishing effort from the MPAs (Sherley et al, 2018). Second, a counterfactual assessment found that the U.S. Pacific Remote Islands Marine National Monument caused a reduction in blue shark catch rates by Hawaii's pelagic longline fishery (Gilman et al, 2020). The Monument was also found to have protected bycatch hotspots for some at-risk species (oceanic whitetip, silky and blue sharks, and olive ridley sea turtle) but cold spots for others (albatrosses, shortfin mako shark and striped marlin).…”
Section: Static Pelagic Marine Protected Areas and Displacement Of The Locally Based Fleetmentioning
confidence: 99%
“…• Mean trophic level of the catch of Hawaii's tuna longline fishery was significantly higher around the U.S. Pacific Remote Islands Marine National Monument than at open ocean fishing grounds (i.e. a larger proportion of the pelagic community that is susceptible to capture in pelagic longline gear in the Monument is made up of top predators than in open ocean areas), suggesting that that the Monument contains a relatively undisturbed pelagic community structure (Gilman et al, 2020) Provide economic benefits • MPAs within the Great Barrier Reef, some of which include pelagic habitat, led to a 35%-36% reduction in catch and ex-vessel value (Fletcher et al, 2015), however, this conclusion is complicated by additional measures to reduce fishing capacity (Hughes et al, 2016 finding that social outcomes arise even in remote MPAs, they arise at all stages, can produce outcomes at a higher level of social organization, and can produce social change processes that lead to social impacts. These social effects of the MPAs may be intended or unintended, positive or negative (Gruby et al, 2017) Real-time, dynamic spatial management…”
Section: Abmt Objective Evidencementioning
confidence: 98%
“…Protect non-target species • A counterfactual assessment found that the U.S. Pacific Remote Islands Marine National Monument caused a reduction in blue shark catch rates by Hawaii's pelagic longline fishery (Gilman et al, 2020). The Monument was also found to have protected bycatch hotspots for some at-risk species (oceanic whitetip (Caracharhinus longimanus, Carcharhinidae), silky (Carcharhinus falciformis, Carcharhinidae) and blue sharks, and olive Ridley sea turtle (Lepidochelys olivacea, Cheloniidae)) but cold-spots for others (albatrosses (Phoebastria spp., Diomedeidae), shortfin mako shark (Isurus oxyrinchus, Lamnidae) and striped marlin; Gilman et al, 2020) • Small MPAs adjacent to African penguin (Spheniscus demersus, Speheniscidae) colonies that removed purse seine fishing for pelagic forage fishes may have improved penguin foraging efficiency, chick survival and condition, and increased population growth at one of the colonies.…”
Section: Abmt Objective Evidencementioning
confidence: 99%
See 1 more Smart Citation